KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN AGAM - Noni Atriani (Universitas Negeri Padang, 2014)
This study to obtain information on employee perceptions of the process, style and effectiveness of decision-making by the leadership at the Department of Education, Youth and Sports Agam. This is a descriptive study. Total population of 66 respondents sample taken is 53% of the total population is 44 people. The technique used is Stratified Profertional Random Sampling Technique. Data collection tool used was a Likert scale. Thus it can be said that the employee perception of the Decision by the Chairman of the Department of Education Youth and Sports Agam is performing quite well (3.4). Kunci : Kinerja Pegawai